2016
DOI: 10.1016/j.surg.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Factors that predict the occurrence of and recovery from non-alcoholic fatty liver disease after pancreatoduodenectomy

Abstract: The non-alcoholic fatty liver disease occurrence rate in patients undergoing pancreatoduodenectomy is high, but in about half of these patients, non-alcoholic fatty liver disease will resolve without any enzyme supplementation. Prophylactic supplementation in the postoperative management of pancreatoduodenectomy patients should be based on risk factors, and therapeutic supplementation should be based on recovery factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 26 publications
4
43
1
Order By: Relevance
“…However, the association between post-gastrectomy complications and the incidence of NAFLD was not obvious in this study. It is reported that the patients who received pancreatic enzyme had a lesser rate of NAFLD compared with patients who did not receive pancreatic enzymes [22]. On the other hand, in our study, administration of pancreatic enzyme did not reduce the incidence of NAFLD.…”
Section: Discussioncontrasting
confidence: 80%
“…However, the association between post-gastrectomy complications and the incidence of NAFLD was not obvious in this study. It is reported that the patients who received pancreatic enzyme had a lesser rate of NAFLD compared with patients who did not receive pancreatic enzymes [22]. On the other hand, in our study, administration of pancreatic enzyme did not reduce the incidence of NAFLD.…”
Section: Discussioncontrasting
confidence: 80%
“…Recently, NAFLD after PD with malnutrition has become increasingly problematic. Studies exploring the mechanism of postoperative NAFLD have reported several risk factors, including pancreas cancer, postoperative diarrhea, blood loss, small remnant pancreatic volume, and a long operative time [5,6,19].…”
Section: Discussionmentioning
confidence: 99%
“…reported that postoperative pancreatic exocrine insufficiency measured by 13C‐labeled mixed triglyceride breath test was closely associated with NAFLD. Pancrelipase delayed‐release supplement (LipaCreon ® 1200 mg/day) could improve exocrine dysfunction and was reported to have a significant beneficial effect on NAFLD after PD 7, 13. However, the prevalence of NAFLD has not decreased since 2012 when we started giving pancrelipase supplements in our hospital.…”
Section: Discussionmentioning
confidence: 99%
“…This steatosis received little interest before the last decade because the patients did not usually have severe hepatic dysfunction clinically even though a few reports documented some cases of hepatic failure after pancreatic resection 8, 9, 10. The prevalence of this steatosis was reported to range from 7.8% to 37%,2, 3, 4, 5, 6, 11, 12 but a few reports are available on the time of occurrence and sequential change in the properties of this complication 13. Etiology of this steatosis may be different from that of conventional nonalcoholic fatty liver disease (NAFLD) related to obesity, dyslipidemia or diabetes mellitus (DM).…”
Section: Introductionmentioning
confidence: 99%